Data processing for photoacoustic microscopy - Narissa Mohammed Isa (2018)
Photoacoustic Microscopy (PAM) is an emerging medical imaging modality that aids in diagnosis or detection of any abnormalities of the body in a microscopic level. Due to depth imaging, PAM allows observation of activities in small components of the body such as the blood vessels. In this report, the development and progress of the Final Year Project (FYP) assigned, Data Processing for Photoacoustic Microscopy, will be elaborated. A list of codes was enhanced to analyze and represent a better visualization of a PAM image from its existing data. There was a need for this enhancement to allow depth imaging of the specimen. To ensure the codes written meets its objective, several experiments were done to create a phantom that is being used as the target specimen when executing the PAM scan. In the later chapters of this report, the results from the conducted experiments and future work will be discussed.